2008
DOI: 10.48102/pi.v16i1.299
|View full text |Cite
|
Sign up to set email alerts
|

La relación entre la percepción de estrés y satisfacción con la vida de morbilidad

Abstract: Se estudió la relación entre la percepción de estrés, bienestar subjetivo y morbilidad en una muestra de 404 estudiantes y profesores universitarios mediante cuestionarios que miden estrés, satisfacción con la vida (SWLS), síntomas psicosomáticos y el autoreporte de enfermedad y consulta médica. Se presentan datos de validación de dos escalas creadas ad hoc. Mediante modelamiento con ecuaciones estructurales se confirmó la relación positiva entre la percepción de estrés y síntomas psicosomáticos y su relación … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The core results from this exploratory study provide preliminary support that the perception of psychological distress is a statistically significant predictor of Life Satisfaction in a sample of Chilean free-market workers (Figure 2). This result is concordant with previous research findings, which have suggested a negative relationship between the perception of psychological distress and Life Satisfaction in young, middle-aged and older adults (Hamarat et al, 2001), hospitality workers (Hayes & Weathington, 2007), college students (Holinka, 2015), and university students and academics (Victorio, 2008) Considering the results, it is possible to assume a model that suggests that psychological distress significantly affects life satisfaction. Decreased levels of stress lead to increased life satisfaction.…”
Section: Psssupporting
confidence: 91%
“…The core results from this exploratory study provide preliminary support that the perception of psychological distress is a statistically significant predictor of Life Satisfaction in a sample of Chilean free-market workers (Figure 2). This result is concordant with previous research findings, which have suggested a negative relationship between the perception of psychological distress and Life Satisfaction in young, middle-aged and older adults (Hamarat et al, 2001), hospitality workers (Hayes & Weathington, 2007), college students (Holinka, 2015), and university students and academics (Victorio, 2008) Considering the results, it is possible to assume a model that suggests that psychological distress significantly affects life satisfaction. Decreased levels of stress lead to increased life satisfaction.…”
Section: Psssupporting
confidence: 91%